Novel Strategies for Preventing Diabetes and Obesity Complications with Natural Polyphenols - Carpene, C.; Gomez-Zorita, S.; Deleruyelle, S.; Carpene, M.A. (Current Medicinal Chemistry, 2015)
During the last years, the list of resveratrol effects has grown in parallel with the number of other members of the polyphenol family described to modulate glucose or lipid handling. In the same time, more than ten human studies on the influence of resveratrol supplementation on two related metabolic diseases, obesity and diabetes, have indicated that impressive beneficial effects co-exist with lack of demonstration of clinical relevance, irrespective of the daily dose ingested (0.075 to 1.5 g per capita) or the number of studied patients. Such contrasting observations have been proposed to depend on the degree of insulin resistance of the patients incorporated in the study. To date, no definitive conclusion can be drawn on the antidiabetic or antiobesity benefits of resveratrol. On the opposite, studies on animal models of diabesity consistently indicated that resveratrol impairs diverse insulin actions in adipocytes, blunting glucose transport, lipogenesis and adipogenesis. Since resveratrol also favours lipolysis and limits the production of proinflammatory adipokines, its administration in rodents results in limitation of fat deposition, activation of hexose uptake into muscle, improvement of insulin sensitivity, and facilitation of glucose disposal. Facing to a somewhat disappointing extrapolation to man of these promising antidiabetic and antiobesity properties, attention must be paid to re-examine resveratrol targets, especially those attainable after polyphenol ingestion and to re-define the responses to low doses. In this context, human adipocytes are proposed as a convenient model for the screening of
Keywords: glucose transport